Oil palm biomass-based activated carbons for the removal of cadmium-a review - Hafizah, Naihi; Rubiyah, Baini; Ibrahim, Yakub (AIMS Press, 2021)
Serious water pollution due to climate change as the consequences of non-ecological wastewater treatment and unsustainable agricultural activities had emerged water scarcity problem. The utilization of oil palm biomass into cadmium adsorbent could play a role in killing two birds with one stone, which is to solve the oil palm biomass disposal issue and cadmium pollution issue. The adsorbent modifications discussed in this review focused on furnace heating and microwave heating as well as the combined methods with chemical activating agents. Among the modification methods, the output of chemical activation followed by microwave-induced irradiation of palm kernel shells (PKS) produced activated carbon with high specific surface area (854.42 m2 /g) and high adsorption capacity, qmax (227.27 mg/g). This review is to provide a comprehensive understanding of cadmium adsorption mechanisms and up-to-date progress of modification technologies for different types of oil palm biomass.